An Analysis of Green Product Development and Marketing Initiatives by Corporate houses across the Continent - Dr. Namita Dixit, Dr. Tazyn Rahman (International Journal of Advanced Science and Technology, 2020)
Together we have to move towards greener pastures. This is the need of the hour and not a choice any more. Increased gravity on the various environmental issues has focused shift in the way corporate go about their strategy building. There has been a change in corporate attitudes towards a green lifestyle of the people. Big Business houses are actively trying in devising their strategic impact on the environment. However, this is not very commonly practiced and is still evolving. Organizations and business however, have seen this change in consumer attitudes and are trying to gain an edge in the competitive market by exploiting the potential in the green market industry. The current study introduces the concept of green marketing and looks into the various ways in which different corporate are relating themselves to the concept of green marketing. A conceptual framework is presented and the information is analyzed on the basis of the framework.